Pharmacokinetics and Safety of Estradiol Valerate Tablet and Its Generic: A Phase 1 Bioequivalence Study in Healthy Chinese Postmenopausal Female Subjects - Zhang L; Li M; Fan L; Liu F; Zhang P; Huang Q; Mai G; Shentu J (Dove Medical Press, 2024)
Li Zhang,1,* Mupeng Li,1,* Lianlian Fan,1 Fangfang Liu,1 Peiwen Zhang,1 Qian Huang,1 Gang Mai,1 Jianzhong Shentu1,2 1Phase 1 Clinical Trial Center, Deyang People's Hospital, Deyang, Sichuan, People's Republic of China; 2Research Center for Clinical Pharmacy, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, Zhejiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianzhong Shentu, Email stjz@zju.edu.cn Gang Mai, Email stdygcp@163.comPurpose: Estradiol valerate (Progynova®) is used as hormone therapy to supplement estrogen deficiency. This study aimed to assess the bioequivalence of an estradiol valerate tablet and its generic form, under fasting and fed conditions.Methods: A randomized, open-label, single-dose, 2-period crossover study was conducted on healthy postmenopausal Chinese female volunteers under fasting and fed conditions. For each period, the subjects received either a 1 mg tablet of estradiol valerate or its generic. Blood samples were collected before dosing and up to 72 hours after administration. Plasma levels of total estrone, estradiol, and unconjugated estrone were quantified using a validated liquid chromatography-tandem mass spectrometry method.Results: A total of 54 volunteers were enrolled in this study. The primary pharmacokinetic parameters, including Cmax, AUC0-t, and AUC0-∞, were similar for the two drugs under both fasting and fed conditions, with 90% confidence intervals for the geometric mean ratios of these parameters, all meeting the bioequivalence criterion of 80- 125%. A total of 48 adverse events (AEs) were reported in the fed study compared with 24 AEs in the fasting study.Conclusion: Estradiol valerate and its generic form were bioequivalent and well tolerated under both fasting and fed conditions.Keywords: bioequivalence, estradiol valerate, postmenopausal, pharmacokinetics, safety